2017
DOI: 10.1002/pssr.201700149
|View full text |Cite
|
Sign up to set email alerts
|

Spin to Charge Conversion at the Conducting TiO2Surface

Abstract: The insulating TiO2 (100) surface was transformed into conducting state after Ar+ ion irradiation, which is due to the formation of oxygen vacancies. The thickness of the conducting layer is about 5 nm according to the transmission electron microscopy, and its surface with a spatial asymmetry hosts Rashba spin–orbit coupling. A permalloy (Py) thin film was then deposited onto the irradiated TiO2 by magnetron sputtering. In this Py/TiO2 sample, an inverse Rashba–Edelstein effect (IREE) induced voltage was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Further studies have even found that dc current and dc voltage can be generated by the rectification effect of high‐frequency magnetization dynamics. This so‐called spin rectification effect (SRE), which is due to nonlinear coupling between an oscillating current and an oscillating resistance in magnetic structures, provides a novel technique for the study of magnetization dynamics by electrical detection. Due to its high sensitivity and feasibility, the SRE has been widely employed to study ferromagnetic resonance (FMR), spin wave resonance, and domain‐wall resonance in different ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have even found that dc current and dc voltage can be generated by the rectification effect of high‐frequency magnetization dynamics. This so‐called spin rectification effect (SRE), which is due to nonlinear coupling between an oscillating current and an oscillating resistance in magnetic structures, provides a novel technique for the study of magnetization dynamics by electrical detection. Due to its high sensitivity and feasibility, the SRE has been widely employed to study ferromagnetic resonance (FMR), spin wave resonance, and domain‐wall resonance in different ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%